Effects of enzyme replacement therapy on pain and health related quality of life in patients with Fabry disease: data from FOS (Fabry Outcome Survey). Issue 3 (2nd March 2005) - Hoffmann, B; Garcia de Lorenzo, A; Mehta, A; Beck, M; Widmer, U; Ricci, R
Abstract : Background: Fabry disease is an X linked lysosomal storage disease caused by deficiency of the lysosomal enzyme α-galactosidase A. This leads to accumulation of globotriaosylceramide in nearly all tissues, including the blood vessels, kidney, myocardium, and nervous system. Symptoms often begin in childhood and include acroparaesthesia, with burning or tingling pain that spreads from the extremities to more proximal sites. Aims: This study set out to evaluate pain and its influence on quality of life in patients with Fabry disease receiving enzyme replacement therapy (ERT) with agalsidase alfa. Methods: Data were obtained from the Fabry Outcome Survey. Pain was measured using the Brief Pain Inventory (BPI), and health-related quality of life (HRQoL) was documented with the European Quality of Life Questionnaire (EQ-5D). Results: The mean (SD) score for "pain at its worst" on the BPI prior to ERT was 5.1 (2.7). One year after commencement of ERT, this had improved by 0.5, and improved by a further 0.6 after 2 years (p<0.05). Similar statistically significant improvements were seen for "pain on average" and "pain now" after 2 years of ERT. The mean HRQoL utility score prior to ERT was 0.66 (0.32). After 12 months of treatment with agalsidase alfa, this had improved to 0.74 (0.26; p<0.05); this improvement was maintained after 2 years. Conclusions: ERT with agalsidase alfa significantly reduces pain and improves quality of life in patients with Fabry disease.